KAJIAN PEMANFAATAN TANDAN KOSONG KELAPA SAWIT (TANKOS) SEBAGAI KATALIS BASA PADA REAKSI TRANSESTERIFIKASI METIL ESTER - Asep Ruchiyat (INOVTEK POLBENG, 2018)
The energy and fuel crisis has occurred since the late1970s. Therefore, in the early 1980, it was assumed that the fuel reserves of the non-renewable sources (petroleum-based fuels) could possibly run out and new alternative sources should be found out. Biodiesel is one alternative renewable and biodegradable energy source that is more eco-friendly compared to petroleum diesel. Statistically, based on the Anava test, the result is 5%. It is proved that the addition of concentrated ash from palm oil waste and the temperature of transesterification reaction significantly effects kinematic viscosity at 25 °C (cp), acid number (mg/gr), and sedimentary water content (%). Meanwhile, mass parameter (gr/cm3) statistically has no significant effect. The quality of methyl esters that is produces especially the parameter of acid has fulfilled the standard quality requirement of biodiesel according to SNI-04-7182-2006 althoughwater content parameter, viscosity or mass has not fulfilled SNI quality standard.